2022
DOI: 10.1590/1808-057x20211415.en
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organizational configurations on startup performance

Abstract: This article aimed to investigate the influence of organizational configurations on startup performance. The gap addressed by the article involved analyzing factors simultaneously, considering the possibility of equifinality with regard to the understanding about startup performance. A survey was conducted of 112 southern Brazilian startups. To compose the configurations, the cluster analysis technique was used. The chi-squared and covariance analysis (ANCOVA) tests were used to identify the effect of organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…The study by Davila et al (2015) indicates a significant positive relationship between MCS adoption and firm value. MCS contributes to the growth of startup companies by using management control methods related to revenue and performance (de Oliveira Silva, Marques, da Silva Faia, & Lavarda, 2022;Dyczkowski & Dyczkowska, 2018;Frare et al, 2022;Gomez-Conde et al, 2019). Furthermore, Lin, Chen, and Lin (2017) found that operational control has a positive correlation with the performance of startup companies.…”
Section: Management Control System and Company Performancementioning
confidence: 99%
“…The study by Davila et al (2015) indicates a significant positive relationship between MCS adoption and firm value. MCS contributes to the growth of startup companies by using management control methods related to revenue and performance (de Oliveira Silva, Marques, da Silva Faia, & Lavarda, 2022;Dyczkowski & Dyczkowska, 2018;Frare et al, 2022;Gomez-Conde et al, 2019). Furthermore, Lin, Chen, and Lin (2017) found that operational control has a positive correlation with the performance of startup companies.…”
Section: Management Control System and Company Performancementioning
confidence: 99%